The Modern Scottish Diaspora: Contemporary Debates and Perspectives - Leith, Murray Stewart; Sim, Duncan (Edinburgh University Press, 2014)
Brings together well-established and emerging scholars from a variety of disciplines to present a contemporary ‘diasporic’ perspective on national affairs for Scotland. The book reflects a growing interest in the subject from academics, policy makers and politicians and the Scottish Government's new diaspora strategy.